2016
DOI: 10.1038/bjc.2016.283
|View full text |Cite
|
Sign up to set email alerts
|

Axillary lymph node micrometastases decrease triple-negative early breast cancer survival

Abstract: Background:Triple-negative breast cancers (TNBCs) are the most deadly form of breast cancer (BC) subtypes. Axillary lymph node involvement (ALNI) has been described to be prognostic in BC taken as a whole, but its prognostic value in each subtype is unclear. We explored the prognostic impact of ALNI and especially of small size axillary metastases in early TNBCs.Methods:We analysed in this multicentre study all patients treated for early TNBC in 12 French cancer centres. We explored the correlation between cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…First, in this retrospective study, we tested the associations between the integrative 3′UTR‐based model with the LNM status rather than true prediction. To evaluate the performance of the model, the data from an independent TNBC cohort, with much higher proportion of nodal involvement (50.3%) than that in real world (22.8%) , was used in this study. The disparity in baseline LNM rate may introduce heterogeneity and lower the performance of the model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, in this retrospective study, we tested the associations between the integrative 3′UTR‐based model with the LNM status rather than true prediction. To evaluate the performance of the model, the data from an independent TNBC cohort, with much higher proportion of nodal involvement (50.3%) than that in real world (22.8%) , was used in this study. The disparity in baseline LNM rate may introduce heterogeneity and lower the performance of the model.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as an invasive surgical procedure, SLNB can cause pain, swelling, bruising, and lymphedema at the surgical site and increase the risk of infection and skin or allergic reactions. A previous study conducted in a large cohort from multicenters reported that 77.2% patients with early TNBC had negative lymph node involvement . Thus, most TNBC patients receive overtreatment via axillary surgery, which increases the surgical comorbidity without survival benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Truong et al49 reported that patients aged <45 years with >25% positive axillary nodes and patients aged ≥45 years with >25% positive axillary nodes, medial tumor location and ER negative were recommended for PMRT in a retrospective analysis including 821 T1–2N1 breast cancer patients. In addition, Houvenaeghel et al50 showed that axillary lymph node involvement is a key prognostic feature for early TNBC when isolated tumor cells were identified in lymph nodes. pN0 cases had longer DFS than pN0(i+)/pN1mic51 (isolated tumor cell [,0.2 mm; pN0(i+], micrometastases [,2 mm; pN1mic]) 50.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Houvenaeghel et al50 showed that axillary lymph node involvement is a key prognostic feature for early TNBC when isolated tumor cells were identified in lymph nodes. pN0 cases had longer DFS than pN0(i+)/pN1mic51 (isolated tumor cell [,0.2 mm; pN0(i+], micrometastases [,2 mm; pN1mic]) 50. What is more, in a subgroup analysis from an article, the authors showed that in patients with a low-risk disease (stages T1–2N0) without PMRT, LVI was the only strong predictor of both LRR and disease recurrence (DR), which causes a significantly higher 5-year LRR rate and 5-year DR rate than those without LVI (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with patients suffering from other breast cancer subtypes, patients with TNBC are more likely to suffer ALN metastasis at the time of initial diagnosis [11]. ALN metastasis is confirmed as the most critical independent risk factor at the time of initial diagnosis of TNBCs [12,13]. Currently, a modified radical mastectomy with ALN dissection is still one of the most effective surgical treatments for patients with local advanced BCs without distant metastasis, especially early-TNBCs [14].…”
Section: Introductionmentioning
confidence: 99%